2010
DOI: 10.1159/000231979
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Analysis of the Human Tyrosylprotein Sulfotransferase-2 Gene in Subjects with Chronic Pancreatitis

Abstract: Background/Aims: Human trypsinogens are post-translationally sulfated on Tyr154 by the Golgi resident enzyme tyrosylprotein sulfotransferase-2 (TPST2). Tyrosine sulfation stimulates the autoactivation of human cationic trypsinogen. Because increased trypsinogen autoactivation has been implicated as a pathogenic mechanism in chronic pancreatitis, we hypothesized that genetic variants of TPST2 might alter the risk for the disease. Methods: We sequenced the 4 protein-coding exons and the adjacent intronic sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Autoactivation of human cationic trypsinogen was somewhat increased by sulfation but a similar effect was not observed with anionic trypsinogen [6] , [8] . Increased trypsinogen autoactivation has been implicated as a pathogenic mechanism in chronic pancreatitis, but a genetic study analyzing human TPST2 variants found no association with chronic pancreatitis [13] . More detailed comparative analysis of non-sulfated and sulfated anionic trypsins did not reveal any appreciable differences with respect to catalytic activity on a variety of substrates, activation by enteropeptidase, proteolytic stability or cellular expression [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Autoactivation of human cationic trypsinogen was somewhat increased by sulfation but a similar effect was not observed with anionic trypsinogen [6] , [8] . Increased trypsinogen autoactivation has been implicated as a pathogenic mechanism in chronic pancreatitis, but a genetic study analyzing human TPST2 variants found no association with chronic pancreatitis [13] . More detailed comparative analysis of non-sulfated and sulfated anionic trypsins did not reveal any appreciable differences with respect to catalytic activity on a variety of substrates, activation by enteropeptidase, proteolytic stability or cellular expression [8] .…”
Section: Introductionmentioning
confidence: 99%